Agama dan Penyelenggaraan Pemerintahan yang Baik - Amir Faisol (Millah: Journal of Religious Studies, 2006)
There are three components to implement a good government. First, government which make conducive law and politic environment: second, private business sector which motivate business fields and prepare occupations field; and third, society which facilitate social-politic interaction and mobilize society participation in economic, social and politic activities. To implement those components, a state caretaker must hold to people mandate and serve their interests and also hold to law supremacy for maintaining a justice and people prosperity. No one be able to implements those components except who has heart of hearts and commits on its, and also has high quality intelligence, emotional, spiritual in work ethos.